Social Cognition in Preschoolers: Effects of Early Experience and Individual Differences - Bulgarelli, Daniela; Molina, Paola (Frontiers in Psychology, 2016)
Social cognition is the way in which people process, remember and use information in social contexts to explain and predict their own behaviour and that of others. Children’s social cognition may be influenced by multiple factors, both external and internal to the child. In the current study, two aspects of social cognition were examined: Theory of Mind (ToM) and Emotion Understanding (EU). The aim of this study was to analyse the effects of type of early care (0-3 years of age), maternal education, parents’ country of birth, and child’s language on the social cognition of 118 Italian preschoolers. To our knowledge, the joint effect of these variables on social cognition has not previously been investigated in the literature. The measures used to collect social cognition and linguistic data were not parent- or teacher-reports, but based on direct assessment of the children through two standardized tests, the Test of Emotion Comprehension and the ToM Storybooks. Relationships among the variables showed a complex pattern. Overall, maternal education and linguistic competence showed a systematic effect on social cognition; the linguistic competence mediated the effect of maternal education. In children who had experienced centre-base care in the first three years of life, the effect of maternal education disappeared, supporting the protective role of centre-base care for children with less educated mothers. The children with native and foreign parents did not significantly differed on the social cognition tasks. Limits of the study, possible educational outcomes and future research lines were discussed.